A Study on Trusted Communication in Wireless Networks - Hemalatha, S (International Journal of Computer Sciences and Engineering, 2025)
Several algorithms are proposed which uses the basic scheme by predistributing random keys into nodes. The drawback is that one pair wise key may be shared by multiple links. Chan et al. presented two schemes. In their q-composite scheme, multiple keys are required to establish a secure link, which makes a trade-off between connectivity and security. In their random pair wise-key scheme, a unique pair wise key is assigned to each node and every one of a random set. This scheme provides high security but poses an upper bound on network size. Du et al. proposed the pair wise key predistribution scheme based on both the basic scheme and Blom’s scheme, from which it inherits the threshold property. On the contrary, our scheme utilizes Blom’s scheme more smoothly